2006
DOI: 10.1007/s11724-006-0001-8
|View full text |Cite
|
Sign up to set email alerts
|

The chronic pain assessment through disability

Abstract: Nous proposons, face à la complexité de l'évaluation de la douleur chronique, le recours à une approche globale proposée par le modèle conceptuel de la Classification québécoise du processus de production du handicap. Nous y intégrons les mécanismes physiopathologiques et psychopathologiques de la douleur chronique, tout en respectant une démarche pluridisciplinaire. Ce type d'approche ouvre le champ thérapeutique et permet de redonner au patient les moyens de recouvrer une autonomie optimale face à la douleur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Also, usual work is completely hampered by chronic pain in 71.7 % of cases. Indeed, several authors have reported that chronic pain disrupts body patterns, reduces overall activity level, and causes intolerance to physical and/or intellectual effort [2,26], chronic pain is, therefore, a source of disability, and major alterations in daily life [2]. Furthermore, due to chronic pain complete sleep discomfort was noted in 38.01 % of cases, several studies prove that chronic pain is significantly associated with sleep disorders and even insomnia in hemodialysis patients [11,18,27,28].…”
Section: Impact Of Chronic Pain On Daily Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Also, usual work is completely hampered by chronic pain in 71.7 % of cases. Indeed, several authors have reported that chronic pain disrupts body patterns, reduces overall activity level, and causes intolerance to physical and/or intellectual effort [2,26], chronic pain is, therefore, a source of disability, and major alterations in daily life [2]. Furthermore, due to chronic pain complete sleep discomfort was noted in 38.01 % of cases, several studies prove that chronic pain is significantly associated with sleep disorders and even insomnia in hemodialysis patients [11,18,27,28].…”
Section: Impact Of Chronic Pain On Daily Lifementioning
confidence: 99%
“…In our study, these aspects are completely affected in 69.80 %, 34.6 % and 34 % respectively. Chronic pain can therefore only be evaluated in a relevant way if it is listened to, observed, but also analyzed through the repercussions that are personal, physical, and psychological, as well as social and professional [26].…”
Section: Impact Of Chronic Pain On Daily Lifementioning
confidence: 99%